PERANCANGAN DAN PEMBUATAN GAME EDUKASI BERBASIS WEB PADA MATA PELAJARAN INFORMATIKA DI SMKN 7 PADANG - Hafizh Zulkariim Fahmi; Yunus, Yuliawati; Pernanda, Doni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to design and develop a web-based educational game for the Informatics subject at SMKN 7 Padang and to determine the feasibility of the developed media in terms of validity, practicality, and effectiveness. The web-based educational game was developed as an interactive learning medium to improve students' learning interest, participation, and understanding of Informatics learning materials while assisting teachers in delivering learning content more effectively. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 30 tenth-grade students of SMKN 7 Padang. Data were collected using validity questionnaires, practicality questionnaires, and effectiveness tests. The validity test conducted by experts showed a percentage of 92.83%, which was categorized as very valid. The practicality test obtained a percentage of 85.42%, which was categorized as practical, while the effectiveness test resulted in a percentage of 84.00%, which was categorized as effective. Based on these findings, it can be concluded that the developed web-based educational game met the criteria of being very valid, practical, and effective, making it suitable for use as a learning medium for the Informatics subject at SMKN 7 Padang.